Reactualising the problem of social engineering and digital security - Kolinko, Maryna; Petryshyn, Halyna; Chumak, Halyna (Skhid, 2024)
The article explores the current aspects of social engineering in the digital age. Social engineering is considered as a strategic technology of constructing new meanings, principles, rules and facts of social interaction. The socio-philosophical concepts of K. Popper, P. Sorokin, and R. Silverstone are analyzed in the context of constructive proposals of social engineering. The application of historical and philosophical intellectual constructs to the practices of social transformations is described in the article. The article reveals the possibilities and limitations of digital technologies in social engineering. The risks of creating new tools and algorithms for manipulation, disorientation of users of virtual technologies by social engineering methods are shown within the framework of the digital security problem. The diversity of views on the essence of social engineering and the analysis of its spheres of application problematize the interpretation of its social role and meaning. The methods of constructing social events and interfering in people's lives require critical evaluation. The implementation of AI in social engineering developments leads to the new risks, which are systematized in the article. They are related to the manipulation of public consciousness, distortion of identification and personalisation methods, financial fraud, and violation of human security.